2013
DOI: 10.1186/1476-4598-12-97
|View full text |Cite
|
Sign up to set email alerts
|

Glyceraldehyde-3-phosphate dehydrogenase gene over expression correlates with poor prognosis in non small cell lung cancer patients

Abstract: BackgroundGlycolysis in presence of oxygen with high glucose consumption is known to be the metabolism of choice in many tumors. In lung cancer this phenomenon is routinely exploited in diagnostic PET imaging of fluorodeoxyglucose uptake, but not much is known about the prognostic capabilities of glycolysis level assessment in resected lung tumor samples.MethodsIn this retrospective study, we used real time polymerase chain reaction(RQ-PCR) to assess the expression level of the gene for Glyceraldehyde 3-phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 32 publications
2
22
0
1
Order By: Relevance
“…Therefore, GAPDH has been widely used as a reference gene in several assays in biochemical and molecular biology, such as Northern blotting, reverse transcriptase‐polymerase chain reaction, and western blotting. More recently, the use of GAPDH as a reference gene has been questioned and challenged by several research groups, after various studies on the changes in GAPDH expression in different cancers . These previous studies suggest that GAPDH may be inaccurate when it is used for normalization of gene expression results in pre‐clinical or clinical cancer studies .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, GAPDH has been widely used as a reference gene in several assays in biochemical and molecular biology, such as Northern blotting, reverse transcriptase‐polymerase chain reaction, and western blotting. More recently, the use of GAPDH as a reference gene has been questioned and challenged by several research groups, after various studies on the changes in GAPDH expression in different cancers . These previous studies suggest that GAPDH may be inaccurate when it is used for normalization of gene expression results in pre‐clinical or clinical cancer studies .…”
Section: Introductionmentioning
confidence: 99%
“…However, in these reports tumour samples were obtained from patients with advanced stages of tumour progression (II-IV) [4,23,37,38], without tumour staging classification [39] or where GAPDH gene but not protein expression was quantified [40,41]. In the present study, we have observed a significant overexpression of GAPDH protein during the tumour onset which is associated with patients in the early stages of disease (stage I) and a better outcome.…”
Section: Discussionsupporting
confidence: 58%
“…Proliferation-Elevated GAPDH protein levels are reported in different types of cancer cells, especially in lung cancer (4,19). As a required enzyme in glycolysis, GAPDH is essential for cell growth in vitro and in vivo.…”
Section: K254q Inhibits the Function Of Gapdh In Supporting Cellmentioning
confidence: 99%